Public service reform and Nigeria’s global competitiveness (2014)
Nigeria’s federal public service had been subjected to a series of reforms since the reinventing government ideas came with the structural adjustment programmes in the late 1980s and became fully embraced in 1999 as part of democratic reforms. More recently, the reforms have been driven by the need to make the public service supportive of the government’s vision of a globally competitive economy. This broad goal of global competitiveness provides a basis for evaluating the reform in the absence of clear indicators for measuring progress. Using a historical institutional approach, the paper provides details of the trajectory of the reforms and argues that there is little evidence that the service has become more professional, efficient and effective with improved capacity to deliver services. A cut in the bloated size of the junior cadre and removal of government provision of fringe benefits to public servants do not appear to have translated into achieving the mix of skills, interest and will that are needed to achieve reform goals. A protracted reform blues is underlined by resistance to reform and the predatory values that animate governance. For reforms to be successful there is need to address the cultural patterns of public life at large. Reforms should include training of public servants as well as civic ethics education addressed to the public and politicians.